Proceedings of the 2017 Federated Conference on Computer Science and Information Systems 2017
DOI: 10.15439/2017f231
|View full text |Cite
|
Sign up to set email alerts
|

OpenMP Thread Affinity for Matrix Factorization on Multicore Systems

Abstract: Abstract-The aim of this paper is to investigate the impact of thread affinity on computing performance for matrix factorization on shared memory multicore systems with hierarchical memory. We consider two parallel block matrix factorizations (LU and WZ) and employ thread affinity to improve their performance. We study decomposition without pivoting and we compare differences between various affinity strategies for diagonally dominant matrices. Our results show that the choice of thread affinity has the measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 4 publications
(4 reference statements)
0
9
0
Order By: Relevance
“…In many numerical algorithms where dependencies between data are very complicated, even such tools as efficient optimizing compilers are not able to transform the code to use the potential of modern processors. The authors of [3], [1], present algorithms for solving systems of equations, trying to improve their performance, in particular in parallel. Improvement in performance was obtained by appropriate transformation of the underlying algorithm using looping tiling and appropriate data structures.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In many numerical algorithms where dependencies between data are very complicated, even such tools as efficient optimizing compilers are not able to transform the code to use the potential of modern processors. The authors of [3], [1], present algorithms for solving systems of equations, trying to improve their performance, in particular in parallel. Improvement in performance was obtained by appropriate transformation of the underlying algorithm using looping tiling and appropriate data structures.…”
Section: Related Workmentioning
confidence: 99%
“…However, to parallelize them efficiently, the programmer has to make some decisions about applying various transformations. An example of such loops is matrix algorithms, like matrix multiplication or different kinds of factorizations, widely investigated in the literature [3], [1].…”
Section: Introductionmentioning
confidence: 99%
“…In this research, we control the thread affinity using the environment variable KMP AFFINITY on CPU and PHI KMP AFFINITY on MIC. We studied the OpenMP thread mapping strategies for matrix decompositions on multicore architectures in our work [3]. The results showed that the choice of scatter has the measurable impact on the executed time of the matrix factorisations on CPU.…”
Section: Thread Mappingmentioning
confidence: 99%
“…There is not a single thread mapping strategy that suits all the applications. We studied the OpenMP thread mapping strategies for matrix decompositions on multicore architectures in our work [3]. The results showed that the choice of thread affinity has the measurable impact on the executed time of the matrix factorisations.…”
mentioning
confidence: 99%
See 1 more Smart Citation